Three Concepts of Rights, Two of Property. (23rd March 2018) - Webb, Charlie
Abstract: Sometimes rights are taken to describe concrete, bottom-line entitlements, sometimes a kind of ground of such entitlements. I suggest that this difference reflects not so much disagreement or uncertainty as to the nature of rights as different applications and senses of the term 'right', each expressing a different idea or concept. Much work on rights is compromised by a failure to distinguish these concepts of a right, nowhere more so than in private law, where it accounts for difficulties lawyers have faced when seeking to distinguish personal ( in personam ) and proprietary ( in rem ) rights.